Is There a Relationship Between Vitamin D Level and Iron Deficiency Anemia in Children? - Emine Özdemir Kaçer; Cengizhan Kılıçaslan (Galenos Publishing House, 2023)
Iron deficiency anemia (IDA) is the most common type of anemia in children and a major cause of morbidity and mortality. Vitamin D deficiency (VDD) is a growing public health issue that has been connected to several chronic diseases, such as osteoporosis, cancer, and metabolic syndrome. Recently, in a meta-analytic study conducted on both children and adults, it was clearly shown that there is a relationship between VDD and the risk of anemia. In this study, we wanted to review the prevalence of vitamin D insufficiency in children with IDA. We conducted a retrospective review of patient records from January 2017 to December 2019 to identify individuals aged 4 months to 18 years who had been diagnosed with IDA. Demographic data, dietary patterns, nutritional supplements, Vitamin D levels, and laboratory tests were recorded. Two hundred thirty girls and 198 boys were enrolled in the study, bringing the total number of patients to 428. The patients had a mean age of 7.24±5.1 months. The distribution of female gender according to vitamin D groups (normal, insufficient, deficient) was 85, 103, and 42, respectively; the male gender is 78, 89, and 31, respectively (p=0.745). No statistically significant difference was found between nutrition categories and vitamin D groups in different age groups (p=0.293; p=0.238; p=0.396). No statistically significant difference was found between continuous quantitative variables such as age, hemoglobin, and ferritin and vitamin D groups in different age groups (p=0.885; p=0.168; p=0.728). There was no significant association observed between the severity of anemia and VDD in children with IDA in our study. In the diagnosis of IDA, it may be useful to look at vitamin D levels by considering the time of admission. Further studies are needed for the association between vitamin D levels and IDA.